2006
DOI: 10.1097/01.olq.0000231960.92850.75
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Specific Antigen to Ascertain Reliability of Self-Reported Coital Exposure to Semen

Abstract: The substantial disagreement between self-reports and measurement of a biologic marker of semen exposure in vaginal specimens substantiates that self-reports of sexual behavior cannot be assumed to be valid measures. Future sexually transmitted infection/HIV and pregnancy prevention studies should confirm the validity of self-reports or use end points that do not rely on self-reported data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
65
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 25 publications
8
65
2
Order By: Relevance
“…Previously conducted studies [2][3][4]7,[12][13][14][15][16] have typically employed only a single PSA assay. Our findings indicated a remarkable consistency of biomarker results regarding the presence or absence of semen exposure across the three PSA assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously conducted studies [2][3][4]7,[12][13][14][15][16] have typically employed only a single PSA assay. Our findings indicated a remarkable consistency of biomarker results regarding the presence or absence of semen exposure across the three PSA assays.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies that have compared PSA measurement with self-reported condom use and use problems suggest that PSA provides a more complete measure of condom failure during vaginal intercourse [13][14][15][16]. Methods for measuring PSA, however, vary in characteristics, performance and cost, and their comparability with respect to assessing condom performance has not been adequately evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Vaginal swab material was eluted and tested for the presence of PSA, as a marker of recent unprotected sexual intercourse (14,15), using the Seratec PSA semiquant assay (Seratec Diagnostica, Göttingen, Germany). A volume of 150 l of the eluted swab suspension was centrifuged for 10 min at 13,000 Ï« g. After centrifugation, 120 l of supernatant was used for testing according to the manufacturer's instructions.…”
Section: Study Participantsmentioning
confidence: 99%
“…While the reasons for misreporting in surveys are well-known (e.g., social desirability bias, recall bias), efforts to identify who is more likely to have discrepancies between self-reported survey data and biomarkers, including PSA, have had little success [12,[19][20][21]. In this study, we found that for several women in Group C (concordant), partner influences played a dominant role in their account of why they had unprotected sex, unlike women in Groups A and B (discordant).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies also show that PSA degrades rapidly in the vagina, returning to baseline levels in 24-48 h after exposure [18]. Studies comparing PSA test results with self-reported sexual behaviors have identified high levels of discordance between the two, confirming concerns about the under-reporting of unprotected sexual activity and over-reporting of condom use [7,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%